Preparation method of multi-layer co-extrusion composite perovskite quantum dot material

Through the preparation method of multi-layer coextruded composite perovskite quantum dot material, the halide mechanism passivation and silicon oxide matrix isolation are used to solve the problem of performance attenuation caused by oxygen oxidation properties of traditional quantum dot materials, and high stability and environmentally friendly quantum dot materials are achieved.

CN119912936AInactive Publication Date: 2025-05-02SHENZHEN TIANNUOTONG OPTOELECTRONICS TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510405446.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-02
Publication Date
2025-05-02
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional solution quantum dot materials cause changes in chemical composition and crystal structure due to the oxidation properties of oxygen molecules, which in turn aggravates the problem of performance attenuation.

Method used

The preparation method of multi-layer coextruded composite perovskite quantum dot material is adopted to passivate the surface of perovskite quantum dots through the halide mechanism, and perform multi-layer coextrusion and composite with the silicon oxide matrix to form a double-layer solid inorganic coated structure to isolate the water and oxygen environment.

Benefits of technology

Effectively reduce defects and dangling bonds on the surface of quantum dots, improve water, oxygen, light and thermal stability, avoid sudden material failure, and achieve environmentally friendly green synthesis.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119912936A_ABST
    Figure CN119912936A_ABST
Patent Text Reader

Abstract

The invention relates to the field of perovskite quantum dot materials, and discloses a preparation method of a multilayer co-extrusion composite perovskite quantum dot material, which comprises the following steps: S1, precursor solution preparation: respectively dissolving a metal halide, an organic amine compound and an organic salt compound in a solvent to prepare a precursor solution; s2, quantum dot growth; rapidly mixing the two precursor solutions, and initiating a reaction to enable the perovskite quantum dots to nucleate and grow; s3, quantum dot purification: purifying the synthesized perovskite quantum dots through a centrifugal machine; s4, passivating the perovskite quantum dots; s5, performing multi-layer co-extrusion compounding; and S6, carrying out post-treatment. The surface of the perovskite quantum dot is passivated through a halide mechanism, and the isolation effect of a silicon oxide substrate is combined, so that the defects and dangling bonds on the surface of the quantum dot can be effectively reduced, the perovskite quantum dot can be effectively isolated from water and oxygen, the quantum dot is prevented from being degraded due to exposure in a water-oxygen environment, and the water-oxygen, light and heat stability of the quantum dot is synergistically improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of perovskite quantum dot materials, and in particular to a method for preparing a multi-layer co-extruded composite perovskite quantum dot material. Background Art

[0002] An intelligent healthy light display integrated system that combines intelligent technology with the concept of healthy lighting display. It uses advanced sensor technology, Internet of Things technology, big data analysis and artificial intelligence algorithms to monitor and analyze ambient light, human activity status and user health data in real time, so as to automatically adjust the lighting brightness, color temperature and spectral distribution, and automatically adjust the display-related parameters to achieve the purpose of optimizing the light environment (display), protecting eyesight and promoting human health. The color rendering index (Ra) is used to evaluate the ability of the light source to restore the color of the object. The higher the color rendering index, the closer the color of the object under the light source is to the real color. Choosing a light source with a high color rendering index can help reduce visual fatigue and improve visual comfort.

[0003] In recent years, the annual shipment of LCD TVs worldwide has remained above 200 million units. New technologies such as quantum dot backlight will extend the life of LCDs by at least 10 years. In the future, as the technology routes such as quantum dot diffusion plates and QLEDs mature, the quantum dot display market is expected to grow rapidly. Looking at the key material fields of the display industry, the peak position of quantum dot emission can be adjusted by regulating the grain size, and the emission wavelength can be continuously adjusted within the visible light range.

[0004] However, traditional quantum dots are solution quantum dots, which are generally coated with organic ligands. Oxygen molecules have strong oxidizing properties and can undergo oxidation reactions with certain elements in quantum dots, changing the chemical composition and crystal structure of quantum dots, further aggravating the problem of quantum dot performance attenuation. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention provides a method for preparing a multilayer co-extruded composite perovskite quantum dot material, which solves the problem that oxygen molecules have strong oxidizing properties and can undergo oxidation reactions with certain elements in quantum dots, changing the chemical composition and crystal structure of the quantum dots and aggravating the attenuation of quantum dot performance.

[0006] To achieve the above objectives, the present invention is implemented by the following technical scheme: A method for preparing a multi-layer co-extruded composite perovskite quantum dot material, comprising the following steps: S1. Preparing a precursor solution: dissolving a metal halide, an organic amine compound and an organic salt compound in a solvent respectively to prepare a precursor solution; S2, quantum dot growth: quickly mixing the two precursor solutions to initiate a reaction, causing the nucleation and growth of perovskite quantum dots; S3, quantum dot purification: purify the synthesized perovskite quantum dots by centrifuge to remove unreacted precursors and impurities; S4, passivation of perovskite quantum dots: passivation of the perovskite quantum dot surface through a halide mechanism; S5, multi-layer co-extrusion composite: passivated perovskite quantum dots and silicon oxide matrix are extruded from different channels for extrusion molding; S6. Post-processing: drying the extruded multilayer composite perovskite quantum dot material.

[0007] Preferably, the metal halide in S1 includes tin iodide, tin bromide, bismuth iodide, cuprous iodide, the organic amine compound in S1 includes methylamine, formamide, n-butylamine, and the organic salt compound in S1 includes ammonium acetate halide, ammonium benzoate halide, and ammonium methanesulfonate halide.

[0008] Preferably, in S2, the two precursor solutions are quickly mixed to make the solution reach a supersaturated state with a supersaturation degree of 1.5-2.0 times.

[0009] Preferably, in S3, the perovskite quantum dot solution after the reaction time reaches 10-30 minutes is placed in a centrifuge to remove the precursor and impurities by centrifugal separation.

[0010] Preferably, the halide in S4 includes ammonium chloride solution, ammonium bromide solution, and ammonium iodide solution. In S4, the halide is added to the perovskite quantum dot solution, and stirred and fully mixed.

[0011] Preferably, in S5, the passivated perovskite quantum dot solution is filtered through a filter, and then the silicon oxide particle suspension is subjected to ultrasonic dispersion treatment, the ultrasonic frequency is 40 kHz, and the treatment time is 10-30 minutes. The perovskite quantum dot solution and the silicon oxide particle suspension are extruded through different channels in the extruder, and converge and fit together at the outlet to be formed under the action of pressure.

[0012] Preferably, after the multilayer composite perovskite quantum dot material is extruded in S6, hot air drying is adopted and the temperature is set at 60°C-100°C.

[0013] Preferably, the time of rapid mixing in S2 is controlled within 1-5 seconds, and the stirring speed during mixing is 1000-3000 rpm.

[0014] Preferably, the heating and drying time in S6 is 1-3 hours, and the material is weighed and monitored every 15-30 minutes, and the monitoring method is electronic balance weighing with an accuracy of 0.01g.

[0015] The present invention provides a method for preparing a multi-layer co-extruded composite perovskite quantum dot material. It has the following beneficial effects: 1. The present invention passivates the surface of perovskite quantum dots through a halide mechanism and combines the isolation effect of a silicon oxide matrix, which can effectively reduce defects and dangling bonds on the surface of quantum dots, effectively isolate perovskite quantum dots from water and oxygen, prevent quantum dots from being degraded due to exposure to a water and oxygen environment, and synergistically improve the water, oxygen, light and thermal stability of quantum dots.

[0016] 2. The precursor solutions used in the present invention do not contain lead metal elements, thus avoiding the potential pollution risk of lead elements to the environment from the source. Through lead-free design, the present invention successfully realizes the green synthesis of perovskite quantum dots, providing a reliable technical basis for the development of environmentally friendly multi-layer co-extruded composite perovskite quantum dot materials.

[0017] 3. The present invention forms a double-layer solid inorganic coating structure by multi-layer co-extrusion compounding of the passivated perovskite quantum dots and the silicon oxide matrix, thereby achieving highly stable inorganic packaging, avoiding sudden failure of the material, and isolating the influence of external water and oxygen. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 It is a flow chart of the present invention. DETAILED DESCRIPTION

[0019] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0020] Please refer to the attached Figure 1 The embodiment of the present invention provides a method for preparing a multilayer co-extruded composite perovskite quantum dot material, comprising the following steps: S1. Preparing a precursor solution: dissolving a metal halide, an organic amine compound and an organic salt compound in a solvent respectively to prepare a precursor solution; S2, quantum dot growth: quickly mixing the two precursor solutions to initiate a reaction, causing the nucleation and growth of perovskite quantum dots; S3, quantum dot purification: purify the synthesized perovskite quantum dots by centrifuge to remove unreacted precursors and impurities; S4, passivation of perovskite quantum dots: passivation of the perovskite quantum dot surface through a halide mechanism; S5, multi-layer co-extrusion composite: passivated perovskite quantum dots and silicon oxide matrix are extruded from different channels for extrusion molding; S6. Post-processing: drying the extruded multilayer composite perovskite quantum dot material.

[0021] Specifically, in step S1, metal halide and organic amine compounds are configured into a precursor solution, and organic salt compounds are configured into a precursor solution to form a uniformly dispersed precursor solution, thereby ensuring that all substances are fully mixed at the molecular level, which helps to prepare perovskite quantum dots with good optical properties and high stability, and provides key reaction raw materials for the subsequent synthesis of perovskite quantum dots.

[0022] In step S2, the stable state of the precursor solution is broken by mixing the two precursor solutions, creating conditions for the nucleation and growth of quantum dots. The two precursor solutions containing different key components are quickly mixed to allow the components to fully contact and initiate a chemical reaction, causing the solution to reach an oversaturated state. The remaining precursor molecules in the solution continue to diffuse and deposit on the surface of the crystal nucleus, causing the crystal nucleus to gradually grow to form perovskite quantum dots. Perovskite quantum dots with good optical properties and stability can be obtained to meet the needs of different application scenarios.

[0023] After the quantum dot synthesis reaction is completed in step S3, the target perovskite quantum dots exist in the reaction system, as well as unreacted precursors and possible impurities. The quantum dots can be separated from these unnecessary substances by using centrifugal force to obtain purer perovskite quantum dots. After removing the unreacted precursors and impurities, the luminescence efficiency of the quantum dots is significantly improved.

[0024] In the process of synthesis and purification of quantum dots in step S4, there will inevitably be a large number of defects and dangling bonds on their surface. The surface of perovskite quantum dots is passivated with a halide matrix and the perovskite is isolated from external water and oxygen with a silicon oxide matrix, synergistically improving the water, oxygen, light and thermal stability.

[0025] In step S5, the passivated perovskite quantum dots are combined with the silicon oxide matrix by multi-layer extrusion to form a double-layer solid inorganic coating, water-oxygen-resistant multi-layer composite perovskite quantum dot material, achieving highly stable solid inorganic encapsulation without sudden failure.

[0026] In step S6, the solvent in the extruded multilayer composite perovskite quantum dot material is removed to allow the material to achieve a stable solid structure, reduce the chemical reaction active sites inside the material, reduce the interaction between the material and external environmental factors, and improve the chemical stability and thermal stability of the material.

[0027] The metal halide in S1 includes tin iodide, tin bromide, bismuth iodide, and cuprous iodide; the organic amine compounds in S1 include methylamine, formamidinium, and n-butylamine; and the organic salt compounds in S1 include ammonium acetate halide, ammonium benzoate halide, and ammonium methanesulfonate halide.

[0028] Specifically, the materials used to make the precursor solution do not contain lead metal elements, which effectively prevents the possible pollution of the environment by lead elements. Without using lead elements, effective synthesis of perovskite quantum dots can still be achieved, laying the foundation for the preparation of environmentally friendly multi-layer co-extruded composite perovskite quantum dot materials.

[0029] In S2, the two precursor solutions are quickly mixed to make the solution supersaturated, with a supersaturation of 1.5-2.0 times.

[0030] Specifically, at 1.5-2.0 times supersaturation, there is enough energy in the solution to prompt the solute molecules to overcome the surface energy barrier and aggregate with each other to form crystal nuclei, making the quantum dot crystal structure more complete.

[0031] S3 places the perovskite quantum dot solution after the reaction time reaches 10-30 minutes in a centrifuge to remove the precursor and impurities by centrifugal separation.

[0032] Specifically, the reaction time is controlled within 10-30 minutes to avoid quantum dot agglomeration or excessive impurities caused by too long reaction time. The perovskite quantum dots will settle to the bottom of the centrifuge tube, while the unreacted precursors and impurities generated during the reaction will remain in the supernatant.

[0033] The halide in S4 includes ammonium chloride solution, ammonium bromide solution, and ammonium iodide solution. In S4, the halide is added to the perovskite quantum dot solution, and stirred and fully mixed to obtain perovskite quantum dots with higher purity.

[0034] In S5, the passivated perovskite quantum dot solution is filtered through a filter, and then the silicon oxide particle suspension is subjected to ultrasonic dispersion treatment, the ultrasonic frequency is 40kHz, and the treatment time is 10-30 minutes. The perovskite quantum dot solution and the silicon oxide particle suspension are extruded through different channels in the extruder, and converge and fit together at the outlet to be formed under the action of pressure.

[0035] Specifically, filtering the passivated perovskite quantum dot solution through a filter can remove agglomerates, large particle impurities and incompletely reacted substances that may exist in the solution. By setting the ultrasonic frequency to 40kHz and the processing time to 10-30 minutes, the particles in the silicon oxide particle suspension can be more evenly distributed. The treated perovskite quantum dot solution and the silicon oxide particle suspension are extruded through different channels in the extruder and formed under the action of pressure. The application of pressure allows the perovskite quantum dot solution and the silicon oxide particle suspension to be tightly combined to form a multilayer composite perovskite quantum dot material with specific structure and performance, achieving two-layer inorganic coating, the inner layer passivating defects, and the outer layer isolating water and oxygen.

[0036] After the multilayer composite perovskite quantum dot material is extruded in S6, hot air drying is adopted and the temperature is set at 60°C-100°C.

[0037] Specifically, hot air can quickly take away the evaporated solvent molecules to ensure the efficiency of the drying process. Under hot air drying conditions of 60℃-100℃, the solvent in the multilayer composite perovskite quantum dot material can evaporate at an appropriate rate, improving the quality and stability of the material and laying a good foundation for the subsequent application of the product.

[0038] The time of rapid mixing in S2 is controlled within 1-5 seconds, and the stirring speed during mixing is 1000-3000 rpm.

[0039] Specifically, the two precursor solutions are mixed within 1-5 seconds and at a stirring speed of 1000-3000 rpm to form a high-quality crystal structure.

[0040] The heating and drying time in S6 is 1-3 hours, and the material is weighed and monitored every 15-30 minutes. The monitoring method is electronic balance weighing with an accuracy of 0.01g.

[0041] Specifically, a drying time of 1-3 hours can usually ensure that the solvent is fully evaporated. The material is weighed every 15-30 minutes using an electronic balance with an accuracy of 0.01g. Through weighing monitoring, the residual solvent in the material can be understood in real time. When the quality of the material no longer changes significantly, it means that the solvent has basically evaporated completely and the drying effect has achieved the expected effect, which helps to improve the product's qualification rate and reliability.

[0042] The following is an introduction in conjunction with specific embodiments:

[0043] Example 1, a method for preparing a multilayer co-extruded composite perovskite quantum dot material, comprising the following steps: (1) Weigh tin iodide and methylamine and dissolve them in anhydrous ethanol. Prepare the first precursor solution by dissolving ammonium acetate iodide in toluene.

[0044] (2) The two precursor solutions were mixed within 3 seconds at a stirring speed of 2000 rpm to make the solution reach 1.8 times supersaturation, and the reaction was initiated for 20 minutes.

[0045] (3) Centrifuge the perovskite quantum dot solution at 5000 rpm for 10 minutes to remove precursors and impurities.

[0046] (4) Add ammonium chloride solution to the purified perovskite quantum dot solution and stir for 30 minutes for passivation.

[0047] (5) The passivated perovskite quantum dot solution is filtered through a water filter, the silicon oxide particles are suspended in deionized water, and ultrasonic dispersion is performed at 40 kHz for 20 minutes. The two are extruded through different channels in the extruder, converged and fitted together at the outlet, and formed under pressure.

[0048] (6) Use hot air drying method, set the temperature to 80°C, dry for 2 hours, and weigh the material once every 20 minutes using an electronic balance with an accuracy of 0.01g to test the water sample stability of calcium peptide quantum dots.

[0049] Example 2 (1) Weigh bismuth iodide and n-butylamine, dissolve them in chloroform to prepare a first precursor solution, and weigh ammonium methanesulfonate iodide, dissolve them in chloroform to prepare a second precursor solution.

[0050] (2) The two precursor solutions were mixed within four seconds at a stirring speed of 1500 rpm to make the solution reach 1.7 times supersaturation, and the reaction was initiated for 25 minutes.

[0051] (3) Centrifuge the perovskite quantum dot solution at 4500 rpm for 12 minutes to remove precursors and impurities.

[0052] (4) Add ammonium iodide solution to the purified perovskite quantum dot solution and stir for 35 minutes for passivation.

[0053] (5) The passivated perovskite quantum dot solution is filtered through a water filter, the silicon oxide particles are suspended in deionized water, and ultrasonic dispersion is performed at 40 kHz for 15 minutes. The two are extruded through different channels in the extruder, converged and fitted together at the outlet, and formed under pressure.

[0054] (6) Use hot air drying method, set the temperature to 90°C, dry for 1.5 hours, and weigh the material once every 15 minutes using an electronic balance with an accuracy of 0.01g to test the water sample stability of calcium peptide quantum dots.

[0055] Example 3 (1) Weigh tin bromide and formamide and dissolve them in toluene to prepare the first precursor solution. Then weigh ammonium benzoate bromide and dissolve it in toluene.

[0056] (2) The two precursor solutions were mixed within two seconds at a stirring speed of 2500 rpm to make the solution reach 1.6 times supersaturation and initiate the reaction. The reaction lasted for 15 minutes.

[0057] (3) Centrifuge the perovskite quantum dot solution at 6000 rpm for 8 minutes to remove precursors and impurities.

[0058] (4) Then, add ammonium bromide solution to the purified perovskite quantum dot solution and stir for 25 minutes for passivation.

[0059] (5) The passivated perovskite quantum dot solution is filtered through a water filter, the silicon oxide particles are suspended in deionized water, and ultrasonic dispersion is performed at 40 kHz for 15 minutes. The two are extruded through different channels in the extruder, converged and fitted together at the outlet, and formed under pressure.

[0060] (6) Use hot air drying method, set the temperature to 70°C, dry for 2.5 hours, and weigh the material once every 25 minutes using an electronic balance with an accuracy of 0.01g to test the water sample stability of calcium peptide quantum dots.

[0061] Water contact angle Light resistance level TGA weight loss starting temperature Prior art 70° 3 150° Example 1 85° 5 180° Example 2 88° 5 190° Example 3 90° 6 200° Through the comparison of the above data, this method for preparing a multi-layer co-extruded composite perovskite quantum dot material can improve the water, oxygen, light and thermal stability of quantum dots.

[0062] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a multilayer co-extruded composite perovskite quantum dot material, characterized in that: The following steps are involved: S1. Preparing a precursor solution: dissolving a metal halide, an organic amine compound and an organic salt compound in a solvent respectively to prepare a precursor solution; S2, quantum dot growth; The two precursor solutions are quickly mixed to initiate a reaction that allows the nucleation and growth of perovskite quantum dots; S3, quantum dot purification: purify the synthesized perovskite quantum dots by centrifuge to remove unreacted precursors and impurities; S4, passivation of perovskite quantum dots: passivation of the perovskite quantum dot surface through a halide mechanism; S5, multi-layer co-extrusion composite: passivated perovskite quantum dots and silicon oxide matrix are extruded from different channels for extrusion molding; S6. Post-processing: drying the extruded multilayer composite perovskite quantum dot material.

2. The method for preparing a multi-layer co-extruded composite perovskite quantum dot material according to claim 1, characterized in that: The metal halide in S1 includes tin iodide, tin bromide, bismuth iodide, and cuprous iodide; the organic amine compound in S1 includes methylamine, formamidinium, and n-butylamine; and the organic salt compound in S1 includes ammonium acetate halide, ammonium benzoate halide, and ammonium methanesulfonate halide.

3. The method for preparing a multi-layer co-extruded composite perovskite quantum dot material according to claim 1, characterized in that: In S2, the two precursor solutions are quickly mixed to make the solution supersaturated, with a supersaturation of 1.5-2.0 times.

4. The method for preparing a multi-layer co-extruded composite perovskite quantum dot material according to claim 1, characterized in that: In S3, the perovskite quantum dot solution after the reaction time reaches 10-30 minutes is placed in a centrifuge to remove the precursor and impurities by centrifugal separation.

5. The method for preparing a multi-layer co-extruded composite perovskite quantum dot material according to claim 1, characterized in that: The halide in S4 includes ammonium chloride solution, ammonium bromide solution, and ammonium iodide solution. In S4, the halide is added to the perovskite quantum dot solution, and stirred to be fully mixed.

6. The method for preparing a multi-layer co-extruded composite perovskite quantum dot material according to claim 1, characterized in that: In the S5, the passivated perovskite quantum dot solution is filtered through a filter, and then the silicon oxide particle suspension is subjected to ultrasonic dispersion treatment, the ultrasonic frequency is 40kHz, and the treatment time is 10-30 minutes. The perovskite quantum dot solution and the silicon oxide particle suspension are extruded through different channels in the extruder, and converge at the outlet to fit each other and are formed under the action of pressure.

7. The method for preparing a multi-layer co-extruded composite perovskite quantum dot material according to claim 1, characterized in that: In the S6, after the multilayer composite perovskite quantum dot material is extruded, hot air drying is adopted and the temperature is set at 60° C.-100° C.

8. The method for preparing a multi-layer co-extruded composite perovskite quantum dot material according to claim 1, characterized in that: The time of rapid mixing in S2 is controlled within 1-5 seconds, and the stirring speed during mixing is 1000-3000 rpm.

9. The method for preparing a multi-layer co-extruded composite perovskite quantum dot material according to claim 7, characterized in that: The heating and drying time in S6 is 1-3 hours, and the material is weighed and monitored every 15-30 minutes. The monitoring method is electronic balance weighing with an accuracy of 0.01g.

Citation Information

Patent Citations

  • Preparation method and application of composite material

    CN111808606A

  • Perovskite metal halide zero-dimensional quantum dot / polymer composite material and preparation method thereof, and application of organic amine salt

    CN114149641A